2002
DOI: 10.1016/s0960-894x(01)00714-4
|View full text |Cite
|
Sign up to set email alerts
|

Potent In vitro methicillin-resistant Staphylococcus aureus activity of 2-(1H-indol-3-yl)tetrahydroquinoline derivatives

Abstract: Novel antibacterials agents, 2-(1H-indol-3-yl)tetrahydroquinolines, were prepared using hetero Diels-Alder chemistry and found to be effective in vitro against methicillin-resistant Staphylococcus aureus (MRSA). A structure-activity relationship (SAR) study was conducted to determine the important features of this series and to increase the potency of these compounds. Compounds were prepared that had minimum inhibitory concentrations (MIC's) < 1.0 microg/mL against MRSA, but had no activity versus vancomycin-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The quinolines (Qs) and their structural analogs are flat aromatic molecules widely distributed in nature that display a wide spectrum of biological activities (Michael, ). Diverse substituted Qs showed therapeutic potential in the treatment of diseases of microbial origin (Urbina et al, ; Buller et al, ; Hoemann et al, ; Jacquemond‐Collet et al, ; Gómez‐Barrio et al, ; Gholap et al, ; Nandhakumar et al, ; Meléndez Gómez et al, ), as well as antitumor (Rodríguez‐Loaiza et al, ; Khan, ; Li et al, ; Loza‐Mejía et al, ) and neuroprotective (Wright et al, ; Di Fabio et al, ) agents. Despite the therapeutic potential of Qs, their use as pharmaceuticals is limited because some of these compounds are carcinogenic in the colon and liver of animal models (Hirao et al, ; Futakuchi et al, ; Saeki et al, ), an effect that has been associated with their mutagenic potency in the corresponding organ (Nagao et al ; Asakura et al, ; Suzuki et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The quinolines (Qs) and their structural analogs are flat aromatic molecules widely distributed in nature that display a wide spectrum of biological activities (Michael, ). Diverse substituted Qs showed therapeutic potential in the treatment of diseases of microbial origin (Urbina et al, ; Buller et al, ; Hoemann et al, ; Jacquemond‐Collet et al, ; Gómez‐Barrio et al, ; Gholap et al, ; Nandhakumar et al, ; Meléndez Gómez et al, ), as well as antitumor (Rodríguez‐Loaiza et al, ; Khan, ; Li et al, ; Loza‐Mejía et al, ) and neuroprotective (Wright et al, ; Di Fabio et al, ) agents. Despite the therapeutic potential of Qs, their use as pharmaceuticals is limited because some of these compounds are carcinogenic in the colon and liver of animal models (Hirao et al, ; Futakuchi et al, ; Saeki et al, ), an effect that has been associated with their mutagenic potency in the corresponding organ (Nagao et al ; Asakura et al, ; Suzuki et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mardenborough et al synthesized several N-substituted quindolines to study the effect of N-alkylation on the antimicrobial activity of selected quindolines. The synthesized compounds were evaluated for their antimicrobial activity against selected bacterial and fungal strains including MRSA which indicated that compound 46 was most potent anti-MRSA agent having IC 50 value of 2.0 µg/mL (Table 24) (Table 26) [48].…”
mentioning
confidence: 99%
“…1 Primarily, various substituted linear furo [2,3-b]quinolines and angular furo [3,2-c]quinolines have attracted considerable attention as a result of their significant role in medicinal chemistry and their presence in a variety of alkaloids. 2,3 This class of compounds mainly isolated from Rutaceae plant family exhibit antiallergic, 4 anti-inflammatory, 4 cytotoxic, 5 platelet aggregation inhibiting, 5 antimicrobial, 6 voltage-gated potassium channel blocking, 7 spasmolytic, 8 antimalarial, 8 and mutagenic 8 activity. In addition, furoquinolines have a long and successful history in the treatment of Alzheimer's disease.…”
mentioning
confidence: 99%